Investment for the demographic window in Latin America - Maria Jose Rodriguez (Banco de México, 2019)
This paper studies the behavior of investment during demographic transitions. In particular, I focus on the period where the working age to population ratio reaches its maximum, namely the demographic window. I document that in Europe, Asia, and Oceania investment rates are higher 15 years before and during the window than in other periods, whereas in Latin America they are lower. To understand the relation between investment and a demographic window, I build an overlapping generations model with demographic change and variable degree of financial openness. Within this framework, I conduct several exercises and counterfactuals involving potential drivers of the investment behavior. I find that the demographic behavior in conjunction with the region-specific financial openness can explain the main pattern of investment for the demographic window in Latin America vis-a-vis Europe and Asia.
Keywords: F21; E22; J10; O54; F41; 330; Investment; Demographic Window; Latin America